Design of the Bartlett and Hartley tests for homogeneity of variances under indeterminacy environment - Aslam, Muhammad (Journal of Taibah University for Science, 2020)
The existing Bartlett's test and Hartley's test under classical statistics can be applied only when all observations in the sample are determined, precise and determinate. In some complex situations, it may not possible to measure the exact observations. In this case, the neutrosophic statistics is applied for the decision. In this paper, we present Bartlett's test and Hartley's test under the neutrosophic statistics. We present the designing for the proposed tests under neutrosophic statistical interval method. We present an example and compare the proposed neutrosophic Bartlett's test and Hartley's test over the existing tests under classical statistics. From the comparative study, we conclude that the proposed tests are quite effective, informative and flexible to be applied under the indeterminate environment.